Discrimination of some European vinegars with protected denomination of origin as a function of their amino acid and biogenic amine content. (21st January 2016) - Chinnici, Fabio; Durán‐Guerrero, Enrique; Riponi, Claudio
Abstract: BACKGROUND: Twenty‐three amino acids and 11 amines were quantified in 37 premium quality European vinegars (traditional balsamic vinegar of Modena, balsamic vinegars of Modena and vinegars of Jerez) by an HPLC‐DAD method after derivatisation with diethyl ethoxymethylenmalonate. Data were assessed in the light of the differences in technology and raw materials. RESULTS: The total amount of amino acids ranged from 136 mg kg −1 to 1450 mg kg −1 in traditional balsamic vinegar of Modena and balsamic vinegar of Modena, respectively. Jerez vinegars had a mean content from 351 mg kg −1 to 921 mg kg −1 . Proline, glycine and γ ‐aminobutyric acid were the main amino acids while isoleucine was only found in balsamic vinegar of Modena at a concentration of <1 mg kg −1 . Traditional balsamic vinegar of Modena had the lowest amount of biogenic amines. However, for all the vinegars, their concentration did not raise health issues. Based on the entire dataset, samples were successfully segregated and classified by means of principal component and cluster analysis. CONCLUSION: The amino acid and amine content in vinegars is influenced by the production process and raw materials. They may potentially contribute in characterising the European premium quality vinegars also for authentication or anti‐fraud purposes. © 2015 Society of Chemical Industry